Design Modeling of the City Environment as an Object of Perception - Tkachuk G. A. (Interactive science, 2020)
the article discusses the need to find new modern approaches to formation of the urban public environment, which has the necessary qualities for the accumulation, development and improvement of the intellectual and psycho-emotional potential of society. The author describes certain distortions and destructive phenomena in the social environment of the city, which lead to negative social reactions. An opinion about the ongoing loss of social identity and degeneration of the aesthetic and creative context in the society’s mentality is expressed. The ways of solving the problems of creating sustainable positive conditions for the transformation of the urban environment are proposed.
Keywords: субкультура; информация; социум; предметно-пространственная среда; ментальность; пространство; информационное пространство; жизненный цикл; виртуальная реальность; городская среда; subculture; Society; information; социосфера; virtual reality; mentality; object-spatial environment; space; urban environment; визуальный образ; сознание человека; природа человека; дизайн-моделирование; эстетический идеал; потребительское общество; реабилитация человека; design modeling; aesthetic ideal; sociosphere; human nature; consumer society; in-formation space; visual image; life cycle; human consciousness; human rehabilitation